1997
DOI: 10.1016/s0014-5793(97)01226-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA base damage and antioxidant enzyme levels in childhood acute lymphoblastic leukemia

Abstract: We have investigated the levels of several antioxidant enzymes and the level of oxidative DNA base damage in lymphocytes of children with acute lymphoblastic leukemia (ALL) and in disease-free children. Children with ALL had just been diagnosed with the disease and had received no therapy prior to obtaining blood samples. A multitude of typical hydroxyl radical-induced base lesions in lymphocyte DNA of children were identified and quantified by gas chromatography-isotope dilution mass spectrometry. Higher leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 32 publications
5
57
0
2
Order By: Relevance
“…For example, in studies on breast carcinomas, the 8-oxodG levels have been reported as being 8 to 17 times higher in comparison with those in healthy breast tissue (Matsui et al, 2000). Elevated levels of 8-oxodG from cancer patients compared with healthy subjects have also been observed in lung cancer (Vulimiri et al, 2000;Shen et al, 2007), basal cell carcinoma (Nishigori et al, 2005), bladder cancer (Kaczmarek et al, 2005), acute lymphoblastic leukaemia (Sentürker et al, 1997), colorectal cancer (Oliva et al, 1997), high grade cervical dysplasia (Romano et al 2000), renal cell carcinoma (Okamoto et al, 1994), prostate cancer (Miyake et al, 2004), gastric intestinal metaplasia (Farinati et al, 2008) and gastric adenocarcinoma (Lee et al, 1998). Evidence from these studies suggests that elevated 8-oxodG levels in these malignant or premalignant diseases compared with healthy individuals would be a sign of increased oxidative stress, impaired antioxidant defence or inadequate repair of oxidatively damaged DNA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in studies on breast carcinomas, the 8-oxodG levels have been reported as being 8 to 17 times higher in comparison with those in healthy breast tissue (Matsui et al, 2000). Elevated levels of 8-oxodG from cancer patients compared with healthy subjects have also been observed in lung cancer (Vulimiri et al, 2000;Shen et al, 2007), basal cell carcinoma (Nishigori et al, 2005), bladder cancer (Kaczmarek et al, 2005), acute lymphoblastic leukaemia (Sentürker et al, 1997), colorectal cancer (Oliva et al, 1997), high grade cervical dysplasia (Romano et al 2000), renal cell carcinoma (Okamoto et al, 1994), prostate cancer (Miyake et al, 2004), gastric intestinal metaplasia (Farinati et al, 2008) and gastric adenocarcinoma (Lee et al, 1998). Evidence from these studies suggests that elevated 8-oxodG levels in these malignant or premalignant diseases compared with healthy individuals would be a sign of increased oxidative stress, impaired antioxidant defence or inadequate repair of oxidatively damaged DNA.…”
Section: Discussionmentioning
confidence: 99%
“…20 For example, ROS may interfere with cytoplasmic and nuclear signal transduction pathways, cause structural alterations in DNA, and modulate genes related to cell proliferation, apoptosis, and differentiation processes. 21 McGinnis et al have shown ceria nanoparticles can prevent retinal degeneration induced by intracellular peroxide molecules. 1 The application of ceria nanoparticles in the treatment of spinal cord injury and other central nervous system-based neuron degenerative diseases 4 has proven the biological importance of nanoceria beyond doubt.…”
Section: Introductionmentioning
confidence: 99%
“…Estas alterações implicam em lesões de DNA gerando processos pré-mutagênicos e podendo levar, em alguns casos, ao câncer [27][28][29][30] . Desta forma, a quantificação de glutationa pode indicar uma possível correlação entre a diminuição das atividades de enzimas antioxidantes, como a glutationa peroxidase, e o aumento nos níveis de bases de DNA lesadas devido ao dano oxidativo, comprovando a hipótese de que reações que levam à formação de radicais livres podem aumentar a quantidade de células malignas 31,32 .…”
Section: Sistemas De Defesa Antioxidanteunclassified
“…Os sistemas enzimáticos envolvem as enzimas do ciclo redox da glutationa, particularmente a glutationa peroxidase. Estudos demonstraram também que outras enzimas antioxidantes, como glutationa redutase e glicose-6-fosfato-dehidrogenase, apresentaram propriedades protetoras similares à glutationa peroxidase 27,39 . Outros sistemas enzimáticos de defesa antioxidantes operando em conjunto com as enzimas citadas anteriormente incluem a superóxido dismutase (SOD), dependente de Cu 2+ e Zn 2+ como cofatores, onde ocorre a dismutação do radical superóxido em peróxido de hidrogênio e oxigênio (Eq.…”
Section: Introductionunclassified